Establishment of living lab for a low-emission food system in Nandi County. The journey begins! - Kibet, Walter; Kachilei, Levy; Mosbei, Thomas; Habermann, Birgit (CGIAR, 2023)
In a world facing pressing challenges related to the food system, the need for innovative food system transformation solutions is more critical than ever. The establishment of a Living Lab for People (LL4P) for Low-Emission Food System Development offers Nandi County the opportunity to explore options for locally led innovations for a sustainable and low-emission food system transformation. The CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+) has recently introduced this concept to stakeholders in Nandi County in collaboration with the Kaimosi Agricultural Training Centre (ATC).